Improving Literacy of Forbidden Selling and Buying in Contemporary Transactions Through Service-Learning Method - Alim, Muhammad Nurul; Marasabessy, Ruslan Husein; Maulana, Irwan; Muchtar, Evan Hamzah; Junaedi, Edy; Hidayat, Wahyu (As-sunnah: Jurnal Pengabdian Masyarakat, 2023)
Sharia economic literacy has not touched much on the practice of illicit buying and selling in contemporary financial transactions. Based on a preliminary survey as well as the request of community leaders, a community service activity that carries out literacy on the said subject is needed to be conducted. The method used is Service-Learning which provides an active learning model, the method of which is not only face-to-face lectures but also provides a sense of responsibility of presentations as part of society. This activity involved 71 participants, of which 51 out of 71 were willing to fill out the questionaire. The result shows that this community service activity has helped participants in understanding prohibited buying and selling in contemporary transactions. The presentation on Sharia provisions in buying and selling improved the awareness and knowledge of illicit transactions. Referring to the activity evaluation, this community service is beneficial, being reflected by the improvement of participants' comprehension and the increased level of literacy before and after the program.